Áreas verdes e serviços públicos de saúde na cidade de Mandaguari, Paraná: 2000 a 2010 - Perehouskei, Nestor Alexandre (2013)
The present work is the development of some research on the importance of urban green areas in the context of public health services in the City of Mandaguari, Paraná. Initially, the data of the Hospital Admission Authorization (HAA) was used in the period from 2000 to 2010, which was provided by the database DATASUL, aiming to identify the most frequent health, whose results pointed to the diseases of the respiratory and circulatory systems, which assume in their treatments, the physical activities that can be performed with use for health, in free public spaces. From an investigative research, under the application of a questionnaire to 362 users, it was found that the mobility of the population determines that the ones who live in some neighborhoods, initially located in areas covered by Basic Health Units (BHU), do not often seek health services at the BHU taken as a reference in their place. To do so, they move to other areas of the city, in search of efficiency in attendance. From this perspective, the accessibility to health services is determined by the quality of the offered services, as the communities do not realize geographical barriers to get to the BHUs. In relation to the public spaces, the interviewed people recognize the importance of green areas to improve the quality of life. 357 out of 362 users (98.6%) consider that the green areas provide some pure, clean and healthy air, as well as it is a great space for physical activities, recreation and others. Five users (1.3%) of the population sampled did not consider the contribution of the green areas for health, because of their lack of information or even the difficulty in associating the themes. In this way, the concept of territory, in relation to the healthcare sector, adopts in its own concept the inclusion of the potentialities that come from the presence of the urban green areas, which contribute to some good living conditions of the involved communities.